Marco introductorio : ¿Cómo se está formando al cuerpo docente centroamericano para enseñar la lectoescritura inicial? Aportes de una investigación regional a partir de cinco estudios de caso - Andrade-Calderón, Paola; Stone, Rebecca; Vijil, Josefina (Universidad de Costa Rica, 2020)
The main obstacle to educational progress in Central America is the insufficient training of their teachers. In general, teacher education programs do not help teachers achieve sufficient mastery of content they will be expected to teach, pedagogical knowledge on how to teach that content in the classroom, and skill development; they are also isolated from the school system and the formulation of educational policies. This article discusses this challenge and explains the conceptual framework, methodology and development of the research that analyzed preservice teacher training in the field of initial literacy (EGL). A qualitative research methodology was used to conduct the study in Guatemala, El Salvador, Honduras, Nicaragua and Costa Rica. The preservice teacher education analysis triangulated information obtained from the following sources: (1) a mapping of the preservice literacy curricula against an evidence-based EGL conceptual framework, (2) interviews with preservice teacher trainers and their students, and (3) observations of preservice teacher training classes. The research provides data about the characteristics of preservice teacher education programs and their implementation, which allows for an analysis of their strengths and gaps. The results indicate that the teachers who will teach EGL in Central America are not receiving the training that prepares them for such an important task and that the preservice programs available are not based on current evidence on EGL learning. The findings have been formulated to promote discussion, in participating institutions, about the adjustments that their programs should undergo to bring EGL teacher training closer to what the scientific evidence recommends. Reflections are also offered to motivate discussion on preservice teacher education policies at the national and regional levels.